MANAJEMEN REKRUTMEN BERBASIS KOMPETENSI SEBAGAI STRATEGI MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA - Fachrunisa, Diah; Mariam, lis; Setyawati, Diyah Pertywi; Ruhimat, Imat (Komunitas Manajemen Kompetitif, 2026)
The increasingly dynamic business environment requires organizations to possess human resources (HR) that are competent, adaptive, and competitive. One strategy to improve the quality of human resources is the implementation of competency-based recruitment management. This study aims to analyze the implementation of competency-based recruitment as a strategy for enhancing HR quality at PT Bank Negara Indonesia (Persero) Tbk, as well as to identify supporting factors, obstacles, and its impact on organizational performance. The research employs a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation studies. The research informants include HR managers, line managers, and newly recruited employees. Data analysis is conducted using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing, with data validity ensured through triangulation. The results indicate that competency-based recruitment improves the alignment between individual competencies and job requirements, strengthens a meritocratic culture, and reduces employee turnover rates. The main supporting factors include top management commitment, the use of digital technology, and collaboration between HR departments and line managers. The obstacles encountered include resistance to change and limited understanding of competency-based methodologies. Overall, competency-based recruitment has proven effective in improving HR quality and supporting the sustainability of organizational strategies in the banking sector. Keywords: Competency-Based Recruitment, Human Resource Management, Banking Sector